Art as social practice : technologies for change - burrough, xtine; Walgren, Judy (Routledge, 2022)
"With a focus on socially engaged art practices in the twenty-first century, this book explores how artists use their creative practices to raise consciousness, form communities, create change, and bring forth social impact through new technologies and digital practices. Suzanne Lacy's Foreword and section introduction authors Anne Balsamo, Harrell Fletcher, Natalie Loveless, Karen Moss, and Stephanie Rothenberg present twenty-five in-depth case studies by established and emerging contemporary artists including Kim Abeles, Christopher Blay, Joseph DeLappe, Mary Beth Heffernan, Chris Johnson, Rebekah Modrak, Praba Pilar, Tabita Rezaire, Sylvain Souklaye, and collaborators Victoria Vesna and Siddharth Ramakrishnan. Artists offer first-hand insight into how they activate methods used in socially engaged art projects from the twentieth century and incorporated new technologies to create twenty-first century, socially engaged, digital art practices. Works highlighted in this book span collaborative image-making, immersive experiences, telematic art, time machines, artificial intelligence, and physical computing. These reflective case studies reveal how the artists collaborate with participants and communities, and have found ways to expand, transform, reimagine and create new platforms for meaningful exchange in both physical and virtual spaces. An invaluable resource for students and scholars of art, technology and new media, as well as artists interested in exploring these intersections"--